Phenotypical properties associated with virulence from clinical isolates belonging to the Candida parapsilosis complex. Issue 8 (25th October 2013) - Abi‐chacra, Érika A.; Souza, Lucieri O.P.; Cruz, Lucas P.; Braga‐Silva, Lys A.; Gonçalves, Diego S.; Sodré, Cátia L.; Ribeiro, Marcos D.; Seabra, Sergio H.; Figueiredo‐Carvalho, Maria H.G.; Barbedo, Leonardo S.; Zancopé‐Oliveira, Rosely M.; Ziccardi, Mariangela; et al.
Abstract The production of virulence attributes in three reference strains and 11 clinical isolates primarily identified as Candida parapsilosis was evaluated. Morphological and phenotypical tests were not able to discriminate among the three species of the C. parapsilosis complex; consequently, molecular methods were applied to solve this task. After employing polymerase chain reaction‐based methods, nine clinical strains were identified as C. parapsilosis sensu stricto and two as C. orthopsilosis. Protease, catalase, and hemolysin were produced by all 14 strains, while 92.9% and 78.6% of strains secreted, respectively, esterase and phytase. No phospholipase producers were detected. Mannose/glucose, N‐acetylglucosamine, and sialic acid residues were detected at the surface of all strains, respectively, in high, medium, and low levels. All strains presented elevated surface hydrophobicity and similar ability to form biofilm. However, the adhesion to inert substrates and mammalian cells was extremely diverse, showing typical intrastrain variations. Overall, the strains showed (1) predilection to adhere to plastic over glass and the number of pseudohyphae was more prominent than yeasts and (2) the interaction process was slightly enhanced in macrophages than fibroblasts, with the majority of fungal cells detected inside them. Positive/negative correlations were demonstrated among the production of these virulence traits in C. parapsilosis complex.